The influence of volleyball on the motivational attitudes of rural students through supplementary education - Musafirov, M.K.; Podkovalnikov, S.L.; Pakhar, V.V. (Theory and Practice of Physical Culture, 2026)
Volleyball, as a team sport, possesses unique potential for increasing the physical activity of rural schoolchildren and forming stable motivational attitudes in them. Regular volleyball classes form a habit of discipline and self-control. Successes in volleyball, even if small, increase self-esteem and confidence in one’s own abilities, which has a positive effect on learning activity and the aspiration for new knowledge.